Comparison of the Cervex-Brush® Combi and the Cytobrush+Ayres Spatula Combination for Cervical Sampling in Liquid-Based Cytology. - Marcelo Simonsen; José Humberto Tavares Guerreiro Fregnani; Júlio Cesar Possati Resende; Márcio Antoniazzi; Adhemar Longatto-Filho; Cristovam Scapulatempo-Neto (PLoS ONE, 2016)
To compare the performance of two cervical collection devices (Cytobrush+Ayres spatula and Cervex-Brush® Combi) for cellular sampling, transformation zone representation and accuracy in diagnosing cervical intraepithelial neoplasia (CIN) 2+.Cervical samples were collected from patients referred to the colposcopy unit of the Barretos Cancer Hospital between September 2013 and October 2014 using one of the two sampling devices. Additionally, colposcopy was performed with or without cervical biopsy and/or endocervical curettage.Biopsy was performed in 670 of the 1,235 patients submitted to colposcopy (54.2%). The Cervex-Brush® Combi was more effective than the Cytobrush with respect to endocervical cells sampling (82.7% versus 74.6%; p = 0.001). Sensitivity was also higher with the Cervex-Brush® Combi (48.6% versus 33.9%; p = 0.023) for predicting CIN2+ when high-grade squamous intraepithelial lesions were detected at cytology.Cervex-Brush® Combi was more effective than Cytobrush+Ayres Spatula for endocervical cells sampling and also had a slightly higher accuracy in predicting histologically CIN2+ lesions in patients with diagnosis of HSIL in cytology.